FLIPPED LEARNING IN ENGLISH AS A FOREIGN LANGUAGE CLASSROOMS: ENHANCING STUDENT ENGAGEMENT AND LANGUAGE ACHIEVEMENT - Dilfuza Shuxratovna; Yusufjanova Muattar Baxrom qizi (TADQIQOTLAR, 2026)
Abstract The rapid development of educational technology has significantly influenced the  field  of  foreign  language  teaching,  leading  to  the  emergence  of  innovative pedagogical approaches that promote active learning and learner autonomy. Among these approaches, flipped learning has gained increasing attention due to its ability to reverse traditional instructional practices by delivering content outside the classroom and  dedicating  classroom  time  to  collaborative  and  communicative  activities.  This paper examines the role of flipped learning in English as a Foreign Language (EFL) education and explores its impact on student engagement and language achievement. It argues that the effectiveness of flipped learning depends on the successful integration of  digital  resources,  pedagogical  planning,  and  learner  participation.  While  the approach  offers  numerous  benefits,  including  increased  interaction,  flexibility,  and autonomy,  challenges  related to  technological  access and  learner  readiness  remain. Ultimately, flipped learning should be viewed as a complementary instructional model that enhances, rather than replaces, traditional language teaching practices.